Mitochondrial DNA genomes of five major Helicoverpa pest species from the Old and New Worlds (Lepidoptera: Noctuidae). Issue 5 (14th February 2019) - Walsh, Tom K.; Perera, Omaththage; Anderson, Craig; Gordon, Karl; Czepak, Cecilia; McGaughran, Angela; Zwick, Andreas; Hackett, Daniel; Tay, Wee Tek
Abstract: Five species of noctuid moths, Helicoverpa armigera, H. punctigera, H. assulta, H. zea, and H. gelotopoeon, are major agricultural pests inhabiting various and often overlapping global distributions. Visual identification of these species requires a great deal of expertise and misidentification can have repercussions for pest management and agricultural biosecurity. Here, we report on the complete mitochondrial genomes of H. assulta assulta and H. assulta afra, H. gelotopoeon, H. punctigera, H. zea, and H. armigera armigera and H. armigera conferta' assembled from high‐throughput sequencing data. This study significantly increases the mitogenome resources for these five agricultural pests with sequences assembled from across different continents, including an H. armigera individual collected from an invasive population in Brazil. We infer the phylogenetic relationships of these five Helicoverpa species based on the 13 mitochondrial DNA protein‐coding genes (PCG's) and show that two publicly available mitogenomes of H. assulta (KP015198 andKR149448 ) have been misidentified or incorrectly assembled. We further consolidate existing PCR‐RFLP methods to cover all five Helicoverpa pest species, providing an updated method that will contribute to species differentiation and to future monitoring efforts of Helicoverpa pest species across different continents. We discuss the value of Helicoverpa mitogenomes to assist with species identification in view of the context of the rapid spread of H. armigera in the New World. With this work, we provide the molecular resources necessary for future studies of the evolutionary history and ecology of these species. Abstract : Five species of noctuid moths, Helicoverpa armigera, H. punctigera, H. assulta, H. zea, and H. gelotopoeon, are major agricultural pests inhabiting various and often overlapping global distributions. Here, we report on the complete mitochondrial genomes of these species assembled from high‐throughput sequencing data. We infer the phylogenetic relationships, consolidate existing PCR‐RFLP methods, and provide the molecular resources necessary for future studies of the evolutionary history and ecology of these species.